2001
DOI: 10.1002/gps.381
|View full text |Cite
|
Sign up to set email alerts
|

The progression of cognitive impairment in dementia with Lewy bodies, vascular dementia and Alzheimer's disease

Abstract: Over 1 year, DLB, VaD and AD patients had similar rates of cognitive decline overall. Apolipoprotein E4 may be an important predictor of more rapid decline in DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 32 publications
6
62
3
2
Order By: Relevance
“…For example, AD and VaD share features involving cerebral hypoperfusion, white matter changes, [165][166][167] pathophysiological markers, 168 -172 genetic links, [173][174][175][176] overlapping symptomatology, and diagnostic criteria of dubious reliability. [177][178][179][180][181][182][183][184][185] Several objective clinical criteria are presently used to distinguish AD from VaD, such as the Alzheimer Disease Diagnostic and Treatment Centers, National Institute of Neurological Disorders and StrokeAssociation Internationale pour la Recherche et l'Enseignement en Neurosciences (NINDS-AIREN), DSM-IV, and the Hachinski Ischemia Score. 186 Of these, the most useful in differentiating VaD from AD appears to be the Hachinski Ischemia Score, 187 if it is assumed that mixed pathology is minimally present.…”
Section: Ad-vad Correlatesmentioning
confidence: 99%
“…For example, AD and VaD share features involving cerebral hypoperfusion, white matter changes, [165][166][167] pathophysiological markers, 168 -172 genetic links, [173][174][175][176] overlapping symptomatology, and diagnostic criteria of dubious reliability. [177][178][179][180][181][182][183][184][185] Several objective clinical criteria are presently used to distinguish AD from VaD, such as the Alzheimer Disease Diagnostic and Treatment Centers, National Institute of Neurological Disorders and StrokeAssociation Internationale pour la Recherche et l'Enseignement en Neurosciences (NINDS-AIREN), DSM-IV, and the Hachinski Ischemia Score. 186 Of these, the most useful in differentiating VaD from AD appears to be the Hachinski Ischemia Score, 187 if it is assumed that mixed pathology is minimally present.…”
Section: Ad-vad Correlatesmentioning
confidence: 99%
“…However, within DLB patients, apolipoprotein E4 may be an important predictor of more rapid decline. [40][41][42][43] Additionally, as discussed above, visual hallucinations and delusions are present in DLB, as well as parkinsonian motor features. Parkinsonism may be present at onset, or develop later, unlike in PD dementia (PDD) where motor symptoms tend to precede cognitive impairment.…”
Section: Clinical Coursementioning
confidence: 86%
“…26,69,70 Use of selective serotonin reuptake inhibitors (SSRIs) for symptoms of anxiety, emotional lability, and depression have also demonstrated benefit, though there is no peer-reviewed evidence. 22,43,71 Tricyclic antidepressants (TCAs) and antispasmotics should be avoided for the potential anticholinergic exacerbations. 70 For REM sleep behavior disorder, clonazepam may be beneficial though it could worsen dementia and alertness.…”
Section: Treatmentmentioning
confidence: 99%
“…C. Ballard in his study on the progression of cognitive impairment in dementia with Lewy bodies, vascular dementia and Alzheimer disease reported that the magnitude of cognitive decline was similar in different types of dementia (20). On the other hand Sultzer DL, in his study entitled "A comparison of psychiatric symptoms in vascular dementia and Alzheimer disease" reported that patients with VD had more cognitive impairment compared to patients with DAT, as indicated by the neurobehavioral rating scale total scores (21).…”
Section: Discussionmentioning
confidence: 99%